Altered Expression of an FT Cluster Underlies a Major Locus Controlling Domestication-Related Changes to Chickpea Phenology and Growth Habit - Ortega, Raul; Hecht, Valerie F. G.; Freeman, Jules S.; Rubio, Josefa; Carrasquilla-Garcia, Noelia; Mir, Reyazul Rouf; Penmetsa, R. Varma; Cook, Douglas R.; Millan, Teresa; Weller, James L. (Frontiers in Plant Science, 2019)
Flowering time is a key trait in breeding and crop evolution, due to its importance for adaptation to different environments and for yield. In the particular case of chickpea, selection for early phenology was essential for the successful transition of this species from a winter to a summer crop. Here we used genetic and expression analyses in two different inbred populations to examine the genetic control of domestication-related differences in flowering time and growth habit between domesticated chickpea and its wild progenitor C. reticulatum. A single major QTL for flowering time under short-day conditions (DTF3A) was mapped to a 59-gene interval on chromosome 3 containing a cluster of three FT genes, which collectively showed upregulated expression in domesticated relative to wild parent lines. An equally strong association with growth habit suggests a pleiotropic effect of the region on both traits. These results indicate the likely molecular explanation for the characteristic early flowering of domesticated chickpea, and the previously-described growth habit locus Hg. More generally, they point to de-repression of this specific gene cluster as a conserved mechanism for achieving adaptive early phenology in temperate legumes.